The structure of mixed surfactants at the air-water interface - Penfold, J; Staples, E; Tucker, I; Thomas, R (Elsevier, 1999)
The structure of the mixed non-ionic surfactant monolayer of monododecyl triethylene glycol (C12E3) and monododecyl octaethylene glycol (C12E8) and of the mixed cationic-non-ionic surfactant monolayer of hexadecytrimethyl ammonium bromide (C16TAB) and monododcyl hexaethylene glycol (C12E6) adsorbed at the air-water interface are described. For the non-ionic surfactant mixture the frustration caused by packing the triethylene and octaethylene glycol headgroups results in a change of the surfactant structure compared to the pure monolayer of either surfactant. In particular the octaethylene glycol group is less extended, and the alkyl chain conformation is altered. Although the structures of the cationic and non-ionic surfactants in the non-ionic-cationic surfactant mixture are similar to those of the pure monolayers at an equivalent area per molecule, the detailed labelling schemes used reveal some changes. In the mixed monolayer the alkyl chains of both surfactants are more extended, and the amount of overlap between the surfactant and solvent distributions is greater. The structure of the C16TAB/C12E6 mixture is contrasted with previously published results for the mixtures sodium dodecyl sulphate (SDS)-dodecanol and dodecyl trimethylammonium bromide (C12TAB)-dodecane, which show an increasing change in position of the non-ionic additive at the interface relative to the solvent distribution with increasing solubility of the non-ionic component. Copyright (C) 1999 Elsevier Science B.V.